PENGARUH ISLAMIC LEADERSHIP DAN ISLAMIC WORK MOTIVATION TERHADAP KEPUASAN KERJA KARYAWAN DI PT. PUNAKAWAN INSPIRA INDONESIA - Novitasari, Rindy; Ahmad Yunadi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Problems in managing the quality of human resources remain a challenge for many companies in Indonesia. Employee job satisfaction plays an important role in improving the quality of human resources. However, in the effort to achieve optimal job satisfaction, there are various influencing factors, including the job itself, salary, supervision, relationships with colleagues, and promotion opportunities. This study aims to examine the effect of Islamic Leadership and Islamic Work Motivation on employee job satisfaction at PT. Punakawan Inspira Indonesia. This research employs a quantitative approach with an associative method. Primary data were collected cross-sectionally through the distribution of questionnaires to the entire research population, resulting in 54 respondents. The data analysis techniques used include the Spearman Rank test and ordinal regression with the assistance of SPSS version 30 software. The results of the study indicate that: (1) Based on the Spearman Rank test, Islamic Leadership has a positive and significant effect on employee job satisfaction. (2) The Spearman Rank test also shows that Islamic Work Motivation has a positive and significant effect on employee job satisfaction. (3) The ordinal regression test shows that both variables simultaneously have a significant effect on employee job satisfaction.